Model Design of Motor Sales Information System in Cv. Jaya Baru Motor - Sepian, Andri (The Eastasouth Management and Business, 2023)
The purpose of this research is to build a system that is expected to facilitate the input of sales data and minimize errors in the sales data processing process. The data collection method used is by means of interviews, observations, and coupled with literature studies that have a relationship with the problem at hand. While the research method used is descriptive qualitative research with the Waterfall model development system. CV. Jaya Baru Motor In transaction data processing and processing activities are still manual, so there are often many errors. The effort to solve this problem is to create a web-based sales information system model.